Religion Identity and Moderation: A Social Psychology Perspective - Muhammad Wahid Nur Tualeka; Akhsanul In’am; Abdul Haris; Muhammad Arfan Muammar (P3I UMSurabaya, 2025)
This article examines the relationship between religion identity and moderation within the context of social psychology, with a focus on the influence of religion identity on individual attitudes and behaviors in a pluralistic society. The social tensions often caused by religious differences highlight the importance of understanding the factors that influence moderation attitudes. This research uses a quantitative method with a survey involving 100 respondents from various religious backgrounds. The findings indicate that individuals with strong religious identities tend to have more moderate views. However, the study also reveals that other factors, such as education level and the intensity of interfaith interactions, also affect moderation attitudes. These findings provide new insights into the role of moderation in maintaining social cohesion and strengthening interfaith relationships in an increasingly plural society. This article is expected to contribute to the understanding of social dynamics and the development of policies that support interfaith harmony.